Fruits of Hippophaë rhamnoides in human leukocytes and Caco-2 cell monolayer models—A question about their preventive role in lipopolysaccharide leakage and cytokine secretion in endotoxemia - Laskowska, Anna K.; Wilczak, Aleksandra; Skowrońska, Weronika; Michel, Piotr; Melzig, Matthias F.; Czerwińska, Monika E. (Frontiers in Pharmacology, 2022)
Preparations from Hippophaë rhamnoides L. (sea buckthorn) have been traditionally used in the treatment of skin and digestive disorders, such as gastritis, gastric and duodenal ulcers, uterine erosions, as well as oral, rectal, and vaginal mucositis, in particular in the Himalayan and Eurasian regions. An influence of an aqueous extract from the fruits of H. rhamnoides (HR) on leakage of lipopolysaccharide (LPS) from Escherichia coli through gut epithelium developed from the human colorectal adenocarcinoma (Caco-2) monolayer in vitro and glucose transporter 2 (GLUT2) translocation were the principal objectives of the study. Additionally, the effect of HR on the production of pro- and anti-inflammatory cytokines (interleukins: IL-8, IL-1β, IL-10, IL-6; tumor necrosis factor: TNF-α) by the Caco-2 cell line, human neutrophils (PMN), and peripheral blood mononuclear cells (PBMC) was evaluated. The concentration of LPS on the apical and basolateral sides of the Caco-2 monolayer was evaluated with a Limulus Amebocyte Lysate (LAL) assay. GLUT2 translocation was evaluated using an immunostaining assay, whereas secretion of cytokines by cell cultures was established with an enzyme-linked immunosorbent (ELISA) assay. HR (500 µg/mL) significantly inhibited LPS leakage through epithelial monolayer in vitro in comparison with non-treated control. The treatment of Caco-2 cells with HR (50-100 µg/mL) showed GLUT2 expression similar to the non-treated control. HR decreased the secretion of most pro-inflammatory cytokines in all tested models. HR might prevent low-grade chronic inflammation caused by metabolic endotoxemia through the prevention of the absorption of LPS and decrease of chemotactic factors released by immune and epithelial cells, which support its use in metabolic disorders in traditional medicine.